1977
DOI: 10.2527/jas1977.4551188x
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Natural Zeolites in Animal Science and Aquaculture

Abstract: 77843. 2The authors are greatly indebted to numerous individuals who have provided unpublished information of their research in animal science and aquaculture, including G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
162
2
25

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(197 citation statements)
references
References 7 publications
8
162
2
25
Order By: Relevance
“…The data of the investigation on chromosome aberrations, some blood parameters and body weight gain suggested that the used clinoptilolite sorbent was practically non-toxic. A lack of toxic effects of clinoptilolite has been also demonstrated by other authors: [2,45,[107][108][109].…”
Section: Toxicity Test For Clinoptilolitementioning
confidence: 78%
See 1 more Smart Citation
“…The data of the investigation on chromosome aberrations, some blood parameters and body weight gain suggested that the used clinoptilolite sorbent was practically non-toxic. A lack of toxic effects of clinoptilolite has been also demonstrated by other authors: [2,45,[107][108][109].…”
Section: Toxicity Test For Clinoptilolitementioning
confidence: 78%
“…The molar Si/Al ratio in clinoptilolites is above 4 [28,29]. Clinoptilolites have a relatively open structure with a total pore volume of approximately 35% [30], and chemical formula (K, Na, Ca, Mg).…”
mentioning
confidence: 99%
“…They have selective adsorption, cation exchange capacity, dehydration-rehydration, and catalysis properties that might make them effective in eliminating heavy metals. The most important feature of them in agricultural application is their ion exchange capability without major changes in structure (Mumpton and Fishman 1977;Street 1994). Pb, Cd, and Hg, which are typical toxic heavy metals, could be captured by zeolite (Kazemian et al 2001;Visa 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such aluminosilicates as natural zeolites and clays are the most popular cheap adsorbents widely applied in industry, environment protection, agriculture, medicine, optics, microelectronics and many other fields [1][2][3][4][5]. The sievemolecular properties, availability of strongly active surface sites, high resistance to acids and other useful properties of zeolites allow the use of them as catalysts in cracking, hydrocracking, isomerization and other processes.…”
Section: Introductionmentioning
confidence: 99%